Pemberdayaan Masyarakat Kampung Wisata Inggris di Desa Adiluhur Kecamatan Adimulyo Kabupaten Kebumen - Setyowati, Ratih; Nurmastiti, Ardela; Nissa', Zulfa Nur Auliatun (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
The welfare of rural communities is still a development goal. On the other hand, rural areas are often synonymous with backwardness and poverty. Empowerment of the poor through community approach and awareness is needed in order to use and have access control in the development of tourist villages. This research can describe the model of empowerment and analyze the supporting factors in the development of tourist village in English Tourism Village of Kebumen. In this research used qualitative method with descriptive design. The location of this research intentionally, in this study which is the location of research is the English Tourism Village of Kebumen located in Adiluhur Village Adimulyo District Kebumen District. The research informants were Adiluhur village government, English Tourism Village of Kebumen manager and Adiluhur village community. Empowerment model applied by the empowerment in English Tourism Village of Kebumen that is empowerment model based on empowerment and model of empowerment based on institutional. This model became a strategy in the development of tourist villages in the English Tourism Village of Kebumen.